Constrained fixed sample search - Roberto Bonilla; Francis Kiraly (Center for Economic Studies and ifo Institute (CESifo), 2019)
We consider a version of the Stigler model of fixed sample price search, where consumer utility depends on whether or not at least one sampled price fulfils a pre-set target.
Keywords: D83; 330; fixed sample search; constrained search